Instruktionen als Teil der Serviceleistung ’Problemlösung’ oder: Von der Schwierigkeit, Kunden zum Instruieren zu instruiren - Henk, Christina (HERMES - Journal of Language and Communication in Business, 2008)
This article deals with instructions as a part of the service ‘problem solving’ and shows the difficulties in instructing customers to instruct. I define service as an additional contribution to a product provided to achieve customer loaylty. Every service contains a communicative part which differs in size and can either have a direct or a supportive function. For the analysis of instructions in the service ‘problem solving’, I use the survey for my doctoral thesis about ‘written servicecommunication’. I cooperated with a company producing tools for the textile industry. The survey includes interviews with and work observations of service employees and questionnaires which were sent to clients. The service ‘problem solving’ shows three kinds of instructions, one of them going from client to service employee, the other two going from service employee to client. Difficulties with the service ‘problem solving’ are mainly founded in failures of these instructions. Several communicative elements turn out to be possible disturbing or success factors for the service and methods of resolution are parts of communication studies (e.g. politeness). Thus, this article shows service communication as an interesting field of research for communication studies and applied linguistics.